IMPLEMENT WORLD EXPERIENCE IN MANAGING THE DEVELOPMENT OF PUBLIC-PRIVATE PARTNERSHIPS - Rybka, Oleh V. (Journal of Strategic Economic Research, 2025)
The article analyzes the world experience in managing the development of public-private partnership, which is a justified form of constructive interaction between business and state power structures. It is determined that the nature of such interaction, its methods and forms may differ depending on the national characteristics and current legislation of the countries of the world. Cooperation between the state and business is carried out in conditions based on historically developed needs and opportunities for the implementation of large-scale socio-economic projects and the reform of economic processes. It is substantiated that in modern economic conditions, various models, forms, and types of implementation of partnership relations between the state and business have developed in world practice. It is established that when implementing public-private partnership projects within the framework of its organizational and legal forms and mechanisms of cooperation, various models of cooperation between state structures and private business enterprises can be involved. They are differentiated depending on the volume of quotas transferred to the private partner in management, investment obligations, financial obligations, principles of risk sharing between partners, responsibility for organizing the work. The features of state regulation of partnership relations with business are determined by contractual relations with private sector enterprises, non-profit and public organizations.